2002
DOI: 10.1007/bf03017908
|View full text |Cite
|
Sign up to set email alerts
|

Un ballonnet de grand volume gêne la perfusion de la muqueuse pharyngienne postérieure réalisée avec le tube d’intubation laryngée

Abstract: P Pu ur rp po os se e: : The laryngeal tube airway (LTA) is a new extraglottic airway device with a large proximal cuff that inflates in the laryngopharynx and a distal conical cuff that inflates in the hypopharynx. We determine the influence of the cuff volume and anatomic location on pharyngeal mucosal pressures for the LTA.M Me et th ho od ds s: : Fifteen fresh cadavers were studied. Microchip sensors were attached to the (anatomic location) anterior, lateral and posterior surface of the distal cuff (hypoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…A patient may be in a neutral or the sniffing position during insertion [5]. When positioned using the recommended intracuff volume of air, the pressures exerted by the cuffs of the LT against the pharyngeal mucosa are smaller than those exerted by the ILMA against the cervical spine [6]. We can thus assume that the amount of pressure exerted by the LT against the cervical vertebrae is less than that exerted by the ILMA.…”
mentioning
confidence: 99%
“…A patient may be in a neutral or the sniffing position during insertion [5]. When positioned using the recommended intracuff volume of air, the pressures exerted by the cuffs of the LT against the pharyngeal mucosa are smaller than those exerted by the ILMA against the cervical spine [6]. We can thus assume that the amount of pressure exerted by the LT against the cervical vertebrae is less than that exerted by the ILMA.…”
mentioning
confidence: 99%
“…In a study using silicon microchips on the supraglottic airway devices where they touch the oropharyngeal wall, Brimacombe et al showed that when mucosal perfusion pressure is higher than 34 cmH 2 O there is a reduction in capillary blood fl ow (30,31). Tissue damage occurs with a reduction in capillary blood fl ow (2).…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that cuff under-inflation leads to inadequate anatomical displacement of the pharyngeal tissues, requiring adjunct procedures to maintain airway patency. As the accepted mucosal perfusion pressure within the oropharyngeal mucosa is 40 mmHg [11,12], a desired intracuff pressure < 50 cmH 2 O (36 mmHg) should be appropriate to allow anatomical displacement and maintain mucosal perfusion.…”
Section: Discussionmentioning
confidence: 99%